2010
DOI: 10.1590/s1679-62252010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment reduces aggression of pearl cichlid, Geophagus brasiliensis, during resident-intruder interactions

Abstract: Among fishes, when residents and intruders fight, residents usually win, most likely because they value the residence more than intruders. We hypothesized that enriched environments increase the value of an area in dispute, causing a resident to more fiercely defend a resource-rich environment than a poor one. However, in the present study, intruder-resident tests with the pearl cichlid, Geophagus brasiliensis, showed environmental enrichment actually reduces aggression and can even lead to co-habitation witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 27 publications
5
40
1
2
Order By: Relevance
“…These proportions were statistically different (Goodman test, between multinomials; G observed = 2.83 > G expected = 1.96, P <0.05 and two-tailed Fisher's exact test, P = 0.029). Furthermore, as shown in our article (Kadry & Barreto, 2010), the frequency of aggressive interactions was significantly lower in the enriched environment compared to the nonenriched environment for both resident (Z = 3.27, p < 0.01) and intruder fish (Z = 2.17, p < 0.05). Moreover, in the nonenriched environment, the frequency of attacks directed by the resident animal was statistically higher than for the frequency of attacks directed by the intruder animals (Z = 2.07, p < 0.05).…”
Section: Letters To Editorsupporting
confidence: 73%
See 2 more Smart Citations
“…These proportions were statistically different (Goodman test, between multinomials; G observed = 2.83 > G expected = 1.96, P <0.05 and two-tailed Fisher's exact test, P = 0.029). Furthermore, as shown in our article (Kadry & Barreto, 2010), the frequency of aggressive interactions was significantly lower in the enriched environment compared to the nonenriched environment for both resident (Z = 3.27, p < 0.01) and intruder fish (Z = 2.17, p < 0.05). Moreover, in the nonenriched environment, the frequency of attacks directed by the resident animal was statistically higher than for the frequency of attacks directed by the intruder animals (Z = 2.07, p < 0.05).…”
Section: Letters To Editorsupporting
confidence: 73%
“…Other possibilities could also be suggested. In the case of our study (Kadry & Barreto, 2010), how can we explain our data differently if EE reduced aggression or led to cohabitation without confrontation in pearl cichlids? We assume that the data should be above expectations, irrespective of how nice expectations should be.…”
Section: Letters To Editormentioning
confidence: 85%
See 1 more Smart Citation
“…higher tenure length, more complex environment) and the more valuable the environment is the stronger the prior-residency effect should be (Nijman & Heuts, 2000;Johnsson & Forster, 2002). Kadry & Barreto (2010) recently reported that in intruderresident tests with pearl cichlid, Geophagus brasiliensis, pairs in environmentally enriched test conditions [an aquarium with two pebbles and a plastic kelp model] showed lower frequencies of aggressive interactions than pairs in nonenriched test conditions [a barren aquarium]. Furthermore, they found that in non-enriched test conditions the frequency of directed attacks by resident fish was higher than that of intruders.…”
Section: Introductionmentioning
confidence: 99%
“…Working with a cichlid, Kadry & Barreto (2010) made reference to our work on another cichlid (Burton's mouthbreeder, Haplochromis burtoni) in intruder-resident tests in enriched and non-enriched conditions (Nijman & Heuts, 2000). They reported that for this species we found the residents to have a greater dominance advantage in environmentally enriched conditions.…”
Section: Introductionmentioning
confidence: 99%